Review of commercially available biomarkers in the diagnosis of prostate cancer - Ostrowska, Magdalena; Handzlik, Iwona; Radomska, Martyna; Ostrowski, Adam (Journal of Education, Health and Sport, 2022)
Introduction Diagnosing prostate cancer is a complex process. Although PSA testing remains the basic laboratory study, new biomarkers and test are evolving quickly. Aim The aim of this review was to summarize available tests and markers for diagnosing prostate cancer. Materials and methods Literature search was conducted using PubMed and Cohrane databases. Results and conclusions Detailed description of ExoDx, PCA3, SelectMDx, Mi-prostate Score, SChLAP1, PSA, PHI, 4K Score tests was presented. Available test ease qualification for a prostate biopsy or observation. Patients should be qualified individually in deciding on a specific test to be performed. Urologists should be aware of each test mechanism and limitations.